2018
DOI: 10.1080/14786419.2018.1425856
|View full text |Cite
|
Sign up to set email alerts
|

Chemical constituents from the flowers of Satsuma mandarin and their free radical scavenging and α-glucosidase inhibitory activities

Abstract: Flowers of Citrus plants are used as mild sedatives and for the treatment of insomnia in traditional medicines. In Japan, tea made from the flowers of Satsuma mandarin is consumed as healthy drink. Hesperidin (1), hesperetin (2), rutin (3), quercetin (4), nicotiflorin (5), eriocitrin (6), narirutin (7), phenylethyl glucoside (8) and unshuoside A (9) were isolated from the MeOH extract of fresh flowers. Structure elucidation of these compounds was performed on the basis of NMR spectroscopic data. Among them, ru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
11
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 11 publications
1
11
0
Order By: Relevance
“…This result further supports that the antioxidant activity of these plants is in agreement with their total phenolic and flavonoid contents, as stated in previous studies [24,32]. Phenolic compounds and flavonoids with unsubstituted hydroxyl groups have been recognized as potent free radical scavengers [33,34]…”
Section: Discussionsupporting
confidence: 90%
“…This result further supports that the antioxidant activity of these plants is in agreement with their total phenolic and flavonoid contents, as stated in previous studies [24,32]. Phenolic compounds and flavonoids with unsubstituted hydroxyl groups have been recognized as potent free radical scavengers [33,34]…”
Section: Discussionsupporting
confidence: 90%
“…On the basis of these data, the structure of 1 was assigned as 2(S)-3',4'-dimethoxy-5,7dihydroxyflavanone 7-O-neohesperidoside ( Figure 1 Results obtained from this study revealed that the flowers of Citrus 'Hebesu' are rich in flavonoids, which were similar to previous reports on flowers of other Citrus plants. For example, compound 2 was reported previously from the flowers of C. sinensis [1] and C. unshiu [3]. Similarly, compounds 5-7 were also reported from the flowers of C. unshiu [3].…”
mentioning
confidence: 67%
“…Previous studies have reported anti-inflammatory activity of 80% ethanol extract of flowers of C. unshiu [4], antioxidative activity of the MeOH extract of flowers of C. grandis 'Tomentosa' [5] and sedative activity of MeOH and CH 2 Cl 2 extracts C. sinensis [1]. Recently, we reported flavonoids with potent free radical scavenging and -glucosidase inhibitory activities and other compounds from the MeOH extract of flowers of Satsuma mandarin (C. unshiu) [3]. Citrus 'Hebesu' is a local cultivar of Citrus plant in Hyuga City of Miyazaki Prefecture, Japan.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Citrus peels are one of the underutilized resources and were considered to be waste products. However, in recent years, Citrus peels and flowers are gaining attraction, as these are reported to contain highly bioactive compounds (Adhikari-Devkota, Elbashir, Watanabe, & Devkota, 2018). Citrus fruits and peels are also used as traditional medicines in different countries for digestive problems, cough, skin inflammation and infection, and muscle pain (Gao, Gao, Zeng, Li, & Liu, 2018;Matsumoto et al, 2017).…”
Section: Likementioning
confidence: 99%